2012
DOI: 10.4330/wjc.v4.i10.288
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing in cardiovascular diseases

Abstract: In the last few years, the advent of next generation sequencing (NGS) has revolutionized the approach to genetic studies, making whole-genome sequencing a possible way of obtaining global genomic information. NGS has very recently been shown to be successful in identifying novel causative mutations of rare or common Mendelian disorders. At the present time, it is expected that NGS will be increasingly important in the study of inherited and complex cardiovascular diseases (CVDs). However, the NGS approach to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…Efforts seeking to improve the state of genome editing for investigating or treating cardiomyopathies and other genetic disorders are actively ongoing. Next-generation sequencing, bioinformatics analyses, clinical discoveries, and basic research are constantly identifying new genes involved in cardiomyopathies, providing novel therapeutic targets for genome editing [120,121]. This includes genes that give rise to non-coding RNA, e.g.…”
Section: Recent Advances In Crispr Genome Editing With Potential For mentioning
confidence: 99%
“…Efforts seeking to improve the state of genome editing for investigating or treating cardiomyopathies and other genetic disorders are actively ongoing. Next-generation sequencing, bioinformatics analyses, clinical discoveries, and basic research are constantly identifying new genes involved in cardiomyopathies, providing novel therapeutic targets for genome editing [120,121]. This includes genes that give rise to non-coding RNA, e.g.…”
Section: Recent Advances In Crispr Genome Editing With Potential For mentioning
confidence: 99%
“…However, for complex diseases such as CVDs, candidate biomarkers based on a single omic data modality suffer from the reproducibility issue. 72 To address this issue, we need to research novel NGS bioinformatics methods that not only can integrate multiple omic data modalities (e.g., genetic variations, transcriptional regulation, and epigenetic modifications), but also can associate heterogeneous omic information with CVD phenotypes. Associations (e.g., correlation and causality) resulted from NGS bioinformatics present a great opportunity for researchers to obtain further insights on disease mechanisms and to improve risk predictions for complex CVDs.…”
Section: The Opportunities Of Ngs For Cvdmentioning
confidence: 99%
“…66 It is expected that NGS will become more important in the study of inherited and complex cardiovascular diseases (CVDs). 67 (For example, recent studies using NGS efficiently and successfully identified frameshift mutations in the SMAD3 gene as the cause of vascular disease in a family with arterial aneurysms and dissections inherited in an autosomal dominant pattern. 68 ) However, the NGS approach to the genetics of CVDs represents a territory, which has not been widely investigated.…”
Section: Genomics and Epigenomicsmentioning
confidence: 99%